Jawabanmu

2014-02-22T21:02:24+07:00
2x - 3 = 17
2x = 20
x = 10
dan
2x - 3 = 7
2x = 10
x = 5

f(2x - 3) = 4x - 7

f(17) = 4(10) - 7 = 33
. f(7) = 4 (5) - 7 = 13
------------------------------ -
........f(17) - f(7) = 20..<-- jawaban

atau
2x - 3 = p
2x = p + 3
x = (p+3)/2

f(2x - 3) = 4x - 7
f(p) = 4 [(p+3)/2] - 7
f(p) = 2 (p+3) - 7
f(p) = 2p + 6 - 7
f(p) = 2p - 1

f(17) = 2(17) - 1 = 33
...f(7) = 2(7) - 1 = 13
--------------------------------- -
........f(17) - f(7) = 20..<-- jawaban
1 5 1
2014-02-22T21:04:47+07:00
f(2x-3) = 4x - 7
jika f(17) maka x = 10
f(17) = 4(10) - 7
f(17) = 40 - 7
f(17) = 33

jika f(7) maka x = 5
f(5) = 4(5) - 7
f(5) = 20 - 7
f(5) = 13

f(17) - f(7) = 33 - 13 = 20
1 5 1